Typical preschoolers' perceptions of augmentative and alternative communication modes of a preschooler with autism spectrum disorder. (2nd January 2021) - Lorah, Elizabeth; Holyfield, Christine; Kucharczyk, Suzanne
Abstract: Understanding typical preschoolers' perceptions of communication modes could help guide augmentative and alternative communication (AAC) intervention for preschoolers with autism spectrum disorder (ASD). This study explored the perceptions of 16 typically developing preschoolers toward an (a) AAC application (app) on a tablet, (b) picture exchange using a binder with printed Picture Communication Symbols TM, and (c) prelinguistic communication used by a preschooler with ASD in a series of videos the preschoolers watched. Using a multi-method design, the study implemented both quantitative (rank ordering and preference selection) and qualitative (interview) methodologies. Quantitative results revealed the typical preschoolers had a clear overall preference for the AAC app, but variation in preference existed when selecting a communication mode to use in specific social scenarios. Qualitative data show the children more easily understood the child with ASD when he used the AAC app and associated tablets with fun, which may have accounted for positive perceptions of this AAC mode. The study is exploratory in nature and limited by its size and scope. However, it provides insights useful for clinicians' understanding not just how typical preschoolers perceive various modes of communication, but also why they may perceive some more favorably than others, in order to tailor intervention accordingly.